2002
DOI: 10.1002/mds.10270
|View full text |Cite
|
Sign up to set email alerts
|

Tc‐99m ethylene cysteinate dimer SPECT in the differential diagnosis of parkinsonism

Abstract: Positron emission tomography (PET) and network analysis have been used to identify a reproducible pattern of regional metabolic covariation that is associated with idiopathic Parkinson's disease (PD). The activity of this PD-related pattern can be quantified in individual subjects and used to discriminate PD patients from atypical parkinsonians. Because PET is not commonly available, we sought to determine whether similar discrimination could be achieved using more routine single photon emission computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 28 publications
3
67
1
Order By: Relevance
“…However, it is important to note that although treatment-mediated changes in PDRP expression correlate significantly with improvement in UPDRS ratings, the metabolic and clinical disease descriptors are not interchangeable. Indeed, intersubject differences in these measures generally have less than 50% of their variability in common, as observed in correlations between PDRP scores and motor UPDRS ratings obtained at baseline or during therapy (e.g., Feigin et al, 2002;Lozza et al, 2004;Trošt et al, 2006). Thus, it is likely that the objective imaging-based network measure may provide unique information about disease severity or the Test-retest reliability of Parkinson's disease-related brain network Y Ma et al treatment response that is not captured by the simpler and more accessible clinical rating scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that although treatment-mediated changes in PDRP expression correlate significantly with improvement in UPDRS ratings, the metabolic and clinical disease descriptors are not interchangeable. Indeed, intersubject differences in these measures generally have less than 50% of their variability in common, as observed in correlations between PDRP scores and motor UPDRS ratings obtained at baseline or during therapy (e.g., Feigin et al, 2002;Lozza et al, 2004;Trošt et al, 2006). Thus, it is likely that the objective imaging-based network measure may provide unique information about disease severity or the Test-retest reliability of Parkinson's disease-related brain network Y Ma et al treatment response that is not captured by the simpler and more accessible clinical rating scales.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that this disease is associated with a specific spatial covariance pattern involving metabolic abnormalities in basal ganglia thalamocortical functional/anatomic pathways (Eidelberg et al, 1994(Eidelberg et al, , 1997. Indeed, this PD-related covariance pattern (PDRP) has been detected in multiple independent patient populations scanned in the resting condition (Moeller et al, 1999;Feigin et al, 2002;Lozza et al, 2004;Asanuma et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…This characteristic pattern (FIG. 1A) 1) has been validated in multiple populations of unmedicated PD patients 4,36,43 ; 2) can be detected early in the disease course 34 ; and 3) correlates consistently with disease severity and duration. 3,44 We also found that PDRP activity correlates with nigrostriatal dopamine deficiency as determined by [ 18 F]-fluorodopa PET 34,45 and with internal pallidal (GPi) single unit activity recorded during surgery.…”
Section: Metabolic Brain Network In Parkinson S Diseasementioning
confidence: 99%
“…1,2 Alternatively, disease-related changes in local brain function can be assessed with generalized tracers for regional cerebral metabolism and blood flow. 3,4 Brain imaging in movement disorders was originally introduced to visualize the pathological changes associated with different clinical syndromes. 5 Subsequently, these techniques have been used in longitudinal studies designed to assess disease progression 6,7 and the effects of potential neuroprotective strategies.…”
Section: Introductionmentioning
confidence: 99%
“…14,28 -31 Of these, the most promising appear to be imaging measures of either brain metabolism with 18 F-fluoro-2-deoxy-Dglucose and positron emission tomography (PET) or of cerebral blood flow as measured with SPECT. 32,33 Studies examining the diagnostic accuracy of these and other methods have been difficult, because they rely on comparisons with the clinical diagnosis (the gold standard), which is known to be inaccurate ϳ15-20% of the time. 34 Ideally, a new diagnostic test for PD should be evaluated by comparing the results with a known postmortem pathological result, but no large-scale study using this method has been reported.…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%